2017
DOI: 10.18793/lcj2017.21.12
|View full text |Cite
|
Sign up to set email alerts
|

Empowering young people to make Positive Choices: Evidence-based resources for the prevention of alcohol and other drug use in Australian schools

Abstract: There is increasing evidence that drug education and prevention programs implemented in schools are effective in reducing alcohol and drug use and associated harm. Despite this, evidence-based programs are not widely implemented in schools. We describe the development and evaluation of Positive Choices, an online portal to improve access to, and implementation of, evidence-based drug education in Australian schools.The portal was developed in consultation with drug and alcohol experts, as well as target users … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…The development process was informed by the latest available literature and data on crystal methamphetamine use [ 2 , 4 , 7 , 8 , 20 - 22 ] and drug education [ 23 ] and was developed in collaboration with community members across Australia and expert collaborators. Development occurred across 3 specific phases, which are outlined below:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The development process was informed by the latest available literature and data on crystal methamphetamine use [ 2 , 4 , 7 , 8 , 20 - 22 ] and drug education [ 23 ] and was developed in collaboration with community members across Australia and expert collaborators. Development occurred across 3 specific phases, which are outlined below:…”
Section: Methodsmentioning
confidence: 99%
“…A key aim of this project was to bring together the best available evidence and resources about crystal methamphetamine rather than creating entirely new material. As such, the next step in the content development process was to review existing resources developed by members of the project team for the Positive Choices portal [ 23 , 25 ]. This portal houses evidence-based drug education resources and factsheets for school students, parents, and teachers, including those related to methamphetamine, which were developed in relation to the latest available literature.…”
Section: Methodsmentioning
confidence: 99%
“…Collaborations between the health and education sectors have demonstrated positive results in reducing adolescent substance use. For example, research exploring the role of a school health coordinator (O'Brien et al, 2010), a nationwide transdisciplinary health promotion approach (Sigfusdottir et al, 2011) and an online substance use prevention support portal for educators (Stapinski et al, 2017) has demonstrated that health agencies engaging with schools in various ways can help to promote the implementation of substance use prevention programs and support schools in preventing and reducing student substance use. The objective of this study was to determine the impact of public health engagement (PHE) in school-based substance use prevention programs on student substance use.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, our 2017 survey of Australian schoolteachers found that <25% of teachers had implemented evidence-based AOD education programs. The study identified lack of confidence, resources, time, and support from school; attitude of parents and students; and difficulty in communicating as the main barriers to implementing programs [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The initiative responds to a call from school principals for support to implement evidence-based AOD prevention resources (Australian National Council on Drugs; 2013) and was developed iteratively with experts and end users. School staff, parents, and students provided input and feedback across two phases (for full details refer to the study by Stapinski et al [ 25 ]): (1) formative consultation to clarify scope and identify user needs and (2) review and feedback on a beta version of the website [ 35 ]. The final website was launched in December 2015 and provides web-based training, support, and access to a centralized database of evidence-based AOD prevention programs, recommendations, and resources [ 25 ].…”
Section: Introductionmentioning
confidence: 99%